MENINGKATKAN KEMAMPUAN GURU DALAM PEMBELAJARAN MELALUI PENDEKATAN TEMATIK DI KELAS RENDAH PADA SDN 1 BILAS KECAMATAN UPAU - Sadiman, Sadiman (Tarbiyah, 2014)
The objective of study are to determine the activity of teacher, student activity and student learning outcomes in learning changes in living organisms through a thematic approach. The data of this study in the form of data learning process and outcome measures of data obtained from direct observation and communication. Sources of data in this study are the students and teachers in the learning process changes in living organisms by using descriptive methods. The first instrument of this study is the researchers themselves who act as data collectors using a supporting instrument observation sheet. Data analysis was performed by following the flow of data analysis that includes data collection, data reduction, data display, and conclusion. The results of the implementation of learning action settlement problems by using the thematic approach in each cycle is always an increase in the first cycle an average of 60% indicator and the second cycle an average of 89% indicator. The conclusion that is expected to improve the performance of professional teachers and improve the quality of learners activities with the implementation of thematic learning.Key words: Thematic approach, activity, learning outcomes